URBAN SPACES AND SUBCULTURAL DYNAMICS IN KLAIPEDA IN 1991–2010 (2) - Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2012)
The main issue discussed in the article is relationship between urban spaces and subcultural identity: what empirical analysis of subcultural places say about social processes in a city? The present study is empirical reconstruction of the dynamics of musical subcultures as spatial phenomena in a post-Soviet city (Klaipeda, Lithuania) and covers two decades of rapid urban changes. In this issue of the journal is published the second part of the study, mainly focusing on spatial and stylistic differentiation of two subcultures - rock and electronic dance music – from 1997 till 2010. This period witness two stages of subcultural dynamics. In 1997–2002 subcultures leave public spaces and escapes from social control, what leads them to exploration and appropriation of new spaces for ritual performances. Rock music and the electronic dance music subcultures appropriates their own spaces in the city and don’t mix identity rituals together. 2003–2010 are marked by inner differentiation of subcultures, fragmentation, ideological purification of subcultural identity, and seclusion of ritual spaces. These transformation processes of subcultural identity and places in Klaipeda are interpreted within the bigger context of urban and ideological changes. Keywords: subculture, youth, urban space, subcultural identity, ideology, Klaipeda, post-Soviet, social changes.